The Role of Founder-Led Leadership in Online Education Organizations (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The fast development of digital technologies has brought an essential change to the global education system, giving rise to educational technology (EdTech) platforms and causing their rapid growth. Online education institutions that have been started by founders have been instrumental in the innovation process, increased access to education, and offered new formats of delivering digital education. This study examines how to establish a founder-led model of management and governance that can take an online education school of a brand to scale, specifically focusing on the issue of balancing between entrepreneurial leadership and long-term organization expansion.